DAMPAK SOSIAL PEMBERIAN HAK MILIK ATAS SATUAN RUMAH SUSUN BAGI WARGA NEGARA ASING PASCA UNDANG-UNDANG CIPTA KERJA - Alfiana, Rita; Purwandhani, Ayu (Lex Jurnalica, 2024)
AbstractLand is a component of the earth's surface that plays an important role in supporting people's lives such as cultural, social, economic, political and legal assets that can be used for the prosperity and welfare of the Indonesia nation. The issuance of Law No. 5 of 1960 concerning the Basic Regulations on Agrarian Principles or referred to as the UUPA aims to prosper and prosper the Indonesia nation. The UUPA expressly stipulates that holders of Indonesian citizenship (WNI) are specifically entitled to land with land conditions of Property Rights (HM), Building Rights (HGB), and Business Use Rights (HGU), while Foreign Citizens (WNA) are specifically given only land rights in the form of Use Rights and Lease Rights. The issuance of Law No. 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law No. 2 of 2022 concerning Job Creation, the ownership of flats is limited to Indonesia, Indonesia legal entities, Foreign Citizens (WNA) who have permits in accordance with the provisions of applicable laws and regulations and are only granted in Special Economic Zones (SEZs), Industrial Zones, Trade Zones and Free Ports, and other economic areas. Regulations regarding the ownership of flats for Foreign Citizens (WNA) contained in the Basic Agrarian Law (UUPA) and the Job Creation Law, there are indications of overlap in the two laws and regulations. To elaborate on this, in this study, the author uses a normative juridical research method with a statute approach. Keywords: Flats, Foreigners, Ownership AbstrakTanah adalah komponen permukaan bumi yang berperan penting dalam menunjang kehidupan masyarakat sebagai aset budaya, sosial, ekonomi, politik dan hukum yang dapat dimanfaatkan bagi kemakmuran dan kesejahteraan bangsa Indonesia. Diterbitkannya UU No. 5 Tahun 1960 tentang Peraturan Dasar Pokok-pokok Agraria atau disebut dengan UUPA bertujuan untuk kemakmuran dan kesejahteraan bangsa Indonesia. UUPA secara tegas mengatur bahwa pemegang kewarganeraan Indonesia (WNI) secara khusus berhak atas tanah dengan kondisi tanah Hak Milik (HM), Hak Guna Bangunan (HGB), serta Hak Guna Usaha (HGU), sedangkan Warga Negara Asing (WNA) diberikan secara khusus hanya hak atas tanah berupa Hak Pakai dan Hak Menyewa. Diterbitkannya UU No. 6 Tahun 2023 tentang Penetapan Peraturan Pemerintah Pengganti UU No. 2 Tahun 2022 tentang Cipta Kerja, kepemilikan rumah susun dibatasi hanya bagi orang Indonesia, badan hukum Indonesia, Warga Negara Asing (WNA) yang mempunyai izin sesuai ketentuan peraturan perundang-undangan yang berlaku serta hanya diberikan di Kawasan Ekonomi Khusus (KEK), Kawasan Industri, Kawasan Perdagangan dan Pelabuhan Bebas, dan kawasan ekonomi lain. Peraturan mengenai kepemilikan satuan rumah susun bagi Warga Negara Asing (WNA) yang terdapat dalam Undang-undang Pokok Agraria (UUPA) dan Undang-Undang Cipta Kerja, terdapat indikasi tumpang tindih dalam kedua peraturan perundang-undangan tersebut. Untuk menguraikan hal tersebut, maka pada penelitian ini penulis menggunakan metode penelitian yuridis normatif dengan pendekatan perundang-undangan (statute approach).Kata Kunci: Satuan Rumah Susun, WNA, Kepemilikan